Patient-Clinician Communication During Cardiology Telemedicine Consultations: A Feasibility Study - Timethia J. Bonner DPM, PhD; Bryant Noss BA; Sharonne N. Hayes MD; Katie Ennis MS; David O. Warner MD; Skye Buckner MPH; Adam J. Milam MD, PhD (Journal of Patient Experience)
While studies have evaluated the utility of telehealth in replacing in-person clinical encounters, there is a dearth of literature examining the quality of patient-physician communication with telehealth encounters. Accordingly, this study assessed the feasibility of using virtual cardiology clinical encounters to examine patient-physician interaction, communication, and perceptions of the clinical encounter. Telemedicine cardiology clinical encounters were audio- and video-recorded following the encounter, patients, and cardiologists completed an electronic survey to assess perceptions of the encounter. Qualitative analysis of the communication and statistical analysis of the survey data was conducted, providing descriptive data. The study included 11 patient-physician dyads; all patients were non-Hispanic White. Cardiologists were more racially and ethnically diverse (63% Asian). Most patients agreed telemedicine was comparable to in-person encounters (85.7%), with all cardiologists reporting that patients appeared satisfied with the encounter. We utilized an assessment tool to examine patient-physician communication in the recorded virtual encounters. This study suggests examining patient-physician communication using virtual clinical encounters is feasible, although there are barriers that need addressing for larger studies.